Tantangan Indonesia Hadapi Politik Global Setelah Pemilu 2024 - Agil Kurniadi (Terekam Jejak Publisher, 2024)
This article outlines Indonesia's future challenges in its efforts to face increasingly uncertain global political conditions. After the completion of the 2024 elections, Indonesia has a new president, Prabowo Subianto. In the new leadership period, Indonesia will be faced with increasingly complex global political problems. World political situations such as the Israel-Palestine and Ukraine-Russia conflicts which do not yet have a solution will pose an indirect political-economic threat to Indonesia. This influences foreign political challenges and Indonesia's domestic conditions. Specifically, the author analyzes Indonesia's challenges into three things: first, the views of world countries towards Indonesia's foreign policy; second, proxy war which will affect domestic political stability; third, the potential for an economic crisis that will affect Indonesia's economic conditions. The author uses a qualitative method with a realist concept approach from Hans Morgenthau. This article concludes that if these three challenges cannot be overcome, Indonesia will experience quite serious security and social shocks.